House of Reliability Costs: Developing Reliability Program Activities. (10th December 2013) - Dror, Shuki; Goos, Peter; De Ketelaere, Bart
<x xml:space="preserve">Abstract</x> Reliability is an important factor in the management, planning, and design of an engineering product. In order to meet the customer's requirements and achieve desired reliability level, different types of activities should be performed by the system developer/manufacturer. These activities have to be listed in corresponding reliability program and include: inspection, spare parts storage/providing, failure analysis, etc. On one hand, each activity from reliability program list requires some cost for its realization. On the other hand, when any activity was not performed, we should expect some losses because of system's failures. This paper presents an innovative method that enables a company to determine its vital activities in reliability program. The method is based on a House of Reliability Costs for translating the system's failure costs into relative importance of corresponding activities listed in the reliability program. A Mean Square Error (MSE) criterion supports the selection of vital reliability program activities. It divides a set of activities in reliability program into two groups: vital few (activities in reliability program) and trivial many. The partition minimizes the overall MSE and so, delineates two homogeneous groups. A case study is presented to illustrate the application of the developed methodology in a warfare system. The vital reliability program activities – treatment routine and spare parts storage – were found to be the best activities for reducing the costs of the warfare failures. Copyright © 2013 John Wiley & Sons, Ltd.